การวิเคราะห์กระบวนการเรียนรู้ของขบวนการเคลื่อนไหวทางสังคมแบบใหม่ในการจัดการทรัพยากรธรรมชาติลุ่มน้ำสาขาตอนบนของประเทศไทย - ภัทร ยืนยง (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The aims of this research are (1) to analyze the learning process of the new social movement in national resource management of the tributaries in the upper part of Thailand; and (2) to seek guidelines for the promotion of the learning process of the new social movement in national resource management of the tributaries in the upper part of Thailand. A qualitative approach by means of the case studies of the natural resources and cultural conservation network in the tributaries of the upper part of Thailand was used in collecting data, involving document study, semi-structured interview, in-depth interview, participant and non-participant observation, as well as focus-group. The findings are as follows: 1) The learning process of the new social movement in natural resource management of the tributaries in the upper part of Thailand is a goal as well as a method. That is, it is the common goal of those people forming the group and learning collaboratively through the group process, including the community network and the networks among tributary basins. The emphasis is on the participatory process of people in various tributaries with an aim in their movements for natural resource management of the tributaries and social acceptance. In addition, the aim of the learning process is to facilitate the collaborative learning of people with their individual, accumulated knowledge and experience. The method found focuses on the collaborative learning through practices, exchanges, and analyses to form guidelines and methods used in natural resource management movement, involving the body of knowledge and wisdoms regarded as social capitals and tributary community culture, applicable to modern knowledge in managing the tributary natural resources. 2) The guidelines for the promotion of the learning process of the new social movement in national resource management of the tributaries in the upper part of Thailand, focusing on practices, are: (1) collaborative learning; (2) creation of a learning space through social devices; (3) promotion of people for their self-management of the learning process; (4) fostering thoughts in natural resource management through the application of the body of knowledge as social capital and tributary culture; and (5) creation, search, accumulation, revival, as well as adaptation of social, cultural, symbolic, and economic capitals for the promotion of the learning process of people for their collaborative movement in natural resource management of the tributaries.